Correlation and high-resolution timing for Paleo-tethys Permian-Triassic boundary exposures in Vietnam and Slovenia using geochemical, geophysical and biostratigraphic data sets - Lan, Luu Thi Phuong; B., Ellwood Brooks; H., Tomkin Jonathan; P., Nestell Galina; K., Nestell Merlynd; T., Ratcliffe Kenneth; Harry, Rowe; Huyen, Dang Tran; Dung, Nguyen Thanh; Thang, Nguyen Chien; et al. (Vietnam Journal of Earth Sciences, 2018)
Two Permian-Triassic boundary (PTB) successions, Lung Cam in Vietnam, and Lukač in Slovenia, have been sampled for high-resolution magnetic susceptibility, stable isotope and elemental chemistry, and biostratigraphic analyses. These successions are located on the eastern (Lung Cam section) and western margins (Lukač section) of the Paleo-Tethys Ocean during PTB time. Lung Cam, lying along the eastern margin of the Paleo-Tethys Ocean provides an excellent proxy for correlation back to the GSSP and out to other Paleo-Tethyan successions. This proxy is tested herein by correlating the Lung Cam section in Vietnam to the Lukač section in Slovenia, which was deposited along the western margin of the Paleo-Tethys Ocean during the PTB interval. It is shown herein that both the Lung Cam and Lukač sections can be correlated and exhibit similar characteristics through the PTB interval. Using time-series analysis of magnetic susceptibility data, high-resolution ages are obtained for both successions, thus allowing relative ages, relative to the PTB age at 252 Ma, to be assigned. Evaluation of climate variability along the western and eastern margins of the Paleo-Tethys Ocean through the PTB interval, using d18O values indicates generally cooler climate in the west, below the PTB, changing to generally warmer climates above the boundary. A unique Black Carbon layer (elemental carbon present by agglutinated foraminifers in their test) below the boundary exhibits colder temperatures in the eastern and warmer temperatures in the western Paleo-Tethys Ocean. References Balsam W., Arimoto R., Ji J., Shen Z, 2007. Aeolian dust in sediment: a re-examination of methods for identification and dispersal assessed by diffuse reflectance spectrophotometry. International Journal of Environment and Health, 1, 374-402. Balsam W.L., Otto-Bliesner B.L., Deaton B.C., 1995. Modern and last glacial maximum eolian sedimentation patterns in the Atlantic Ocean interpreted from sediment iron oxide content. Paleoceanography, 10, 493-507. Berggren W.A., Kent D.V., Aubry M-P., Hardenbol J., 1995. Geochronology, Time Scales and Global Stratigraphic Correlation. SEPM Special Publication #54, Society for Sedimentary Geology, Tulsa, OK, 386p. Berger A., Loutre M.F., Laskar J., 1992. Stability of the astronomical frequencies over the Earth’s history for paleoclimate studies. Science, 255, 560-566. Bloemendal J., deMenocal P., 1989. Evidence for a change in the periodicity of tropical climate cycles at 2.4 Myr from whole-core magnetic susceptibility measurements. Nature, 342, 897-900. Chen J., Shen S-j., Li X-h., Xu Y-g., Joachimski M.M., Bowring S.A., Erwin D.H., Yuan D-x., Chen B., Zhang H., Wang Y., Cao C-q, Zheng Q-f., Mu L., 2016. High-resolution SIMS oxygen isotope analysis on conodont apatite from South China and implications for the end-Permian mass extinction. Palaeogeography, Palaeoclimatology, Palaeoecology, 448, 26-38. Da Silva A-C., Boulvain F., 2002. Sedimentology, magnetic susceptibility and isotopes of a Middle Frasnian carbonate platform: Tailfer Section, Belgium. Facies, 46, 89-102. Da Silva A.-C., Boulvain F., 2005. Upper Devonian carbonate platform correlations and sea level variations recorded in magnetic susceptibility. Palaeogeography, Palaeoclimatology, Palaeoecology, 240, 373-388. Dettinger M.D., Ghil M., Strong C.M., Weibel W., Yiou P., 1995. Software expedites singular-spectrum analysis of noisy time series. EOS. Transactions of the American Geophysical Union, 76, 12-21. Dinarès-Turell J., Baceta J.I., Bernaola G., Orue-Etxebarria X., Pujalte V., 2007. Closing the Mid-Palaeocene gap: Toward a complete astronomically tuned Palaeocene Epoch and Selandian and Thanetian GSSPs at Zumaia (Basque Basin, W Pyrenees). Earth Planetary Science Letters, 262, 450-467. Ellwood B.B., García-Alcalde J.L., El Hassani A., Hladil J., Soto F.M., Truyóls-Massoni M., Weddige K., Koptikova L., 2006. Stratigraphy of the Middle Devonian Boundary: Formal Definition of the Susceptibility Magnetostratotype in Germany with comparisons to Sections in the Czech Republic, Morocco and Spain. Tectonophysics, 418, 31-49. Ellwood B.B., Wang W.-H., Tomkin J.H., Ratcliffe K.T., El Hassani A., Wright A.M., 2013. Testing high resolution magnetic susceptibility and gamma gradiation methods in the Cenomanian-Turonian (Upper Cretaceous) GSSP and near-by coeval section. Palaeogeography, Palaeoclimatology, Palaeoecology, 378, 75-90. Ellwood B.B., Wardlaw B.R., Nestell M.K., Nestell G.P., Luu Thi Phuong Lan, 2017. Identifying globally synchronous Permian-Triassic boundary levels in successions in China and Vietnam using Graphic Correlation. Palaeogeography, Palaeoclimatology, Palaeoecology, 485, 561-571. Ghil M., Allen R.M., Dettinger M.D., Ide K., Kondrashov D., Mann M.E., Robertson A., Saunders A., Tian Y., Varadi F., Yiou P., 2002. Advanced spectral methods for climatic time series. Reviews of Geophysics, 40, 3.1-3.41. http://dx.doi.org/10.1029/2000RG000092. Gradstein F.M., Ogg J.G., Smith A.G., 2004. A geologic Time Scale 2004. Cambridge University Press, England, 589p. Hartl P., Tauxe L., Herbert T., 1995. Earliest Oligocene increase in South Atlantic productivity as interpreted from “rock magnetics” at Deep Sea drilling Site 522. Paleoceanography, 10, 311-326. Imbrie J., Hays J.D., Martinson D.G., McIntyre A., Mix A.C., Morley J.J., Pisias N.G., Prell W.L., Shackleton N.J., 1984. The Orbital Theory of Pleistocene Climate: Support from a Revised Chronology of the Marine Delta 18O Record. In Berger A.L., Imbrie J., Hays J., Kukla G., Saltzman B. (Eds.), Milankovitch and Climate, Part I, Kluwer Academic Publishers, 269-305. Mead G.A., Yauxe L., LaBrecque J.L., 1986. Oligocene paleoceanography of the South Atlantic: paleoclimate implications of sediment accumulation rates and magnetic susceptibility. Paleoceanography, 1, 273-284. Salvador A., (Ed.), 1994. International Stratigraphic Guide: The International Union of Geological Sciences and The Geological Society of America, Inc., 2nd Edition, 214p. Scotese C.R., 2001. Atlas of Earth History, Volume 1, Paleogeography, PALEOMAP Project, Arlington, Texas, 52p. Scotese C.R., 2013. Map Folio 49, Permo-Triassic Boundary (251 Ma), PALEOMAP PaleoAtlas for ArcGIS, Triassic and Jurassic Paleogeographic, Paleoclimatic and Plate Tectonic Reconstructions, PALEOMAP Project, Evanston, IL, 3. Shackleton N.J., Crowhurst S.J., Weedon G.P., Laskar J., 1999. Astronomical calibration of Oligocene-Miocene time. Philosophical Transactions of the Royal Society London, A357, 1907-1929. Shaw A.B., 1964. Time in Stratigraphy. New York, Mc Graw Hill, 365p. Shen S.-Z., Crowley J.L., Wang Y., Bowring S.A., Erwin D.H., Henderson C.M., Ramezani J., Zhang H., Shen Y.,Wang X.-D., Wang W., Mu L., Li W.-Z., Tang Y.-G., Liu X.-L., Liu X.-L., Zeng Y., Jiang Y.-F., Jin Y.-G., 2011a. High-precision geochronologic dating constrains probable causes of Earth’s largest mass extinction. Science, 334, 1367-1372. Doi:10.1126/science.1213454. Swartzendruber L.J., 1992. Properties, units and constants in magnetism. Journal of Magnetic Materials, 100, 573-575. Weedon G.P., Jenkyns H.C., Coe A.L., Hesselbo S.P., 1999. Astronomical calibration of the Jurassic time-scale from cyclostratigraphy in British mudrock formations. Philosophical Transactions of the Royal Society London, A357, 1787-1813. Weedon G.P., Shackleton N.J., Pearson P.N., 1997. The Oligocne time scale and cyclostratigraphy on the Ceara Rise, western equatorial Atlantic. In: Schackleton N.J., Curry W.B., Richter C., and Bralower T.J. (Eds.). Proceedings of the Ocean Drilling Program, Scientific Results, 154, 101-114. Whalen M.T., Day J.E., 2008. Magnetic Susceptibility, Biostratigraphy, and Sequence Stratigraphy: Insights into Devonian Carbonate Platform Development and Basin Infilling, Western Alberta. Papers on Phanerozoic Reef Carbonates in Honor of Wolfgang Schlager. SEPM (Society for Sedimentary Geology) Special Publication, 89, 291-314.